A sustentabilidade e seu caráter fundamental à luz do pensamento Marxista - SILVA, Kézia Barbosa da (Universidade Federal do Pará, 2017)
The research aims at the analysis of sustainability and is fundamental character in Brazilian law in the light of Marxixt thought, focusing on anthopocentrism paradigms, ecocentrism and sustainnability-centrism. To this end, we use the bibliographical research and the method of content analysis, takin as reference the Marxixt thought jOHN bELLAMY Foster Constitution and infra-constitutional laws. We analyzed the correlation of sustentainability with the principle of human dignity, with the constitucional principle of the anthropocentrism, ecocentrism and sustaincentrism paradigms, the the analysis of perpective, that demonstrates the effects of the capitalist mode of production inthe relationship man-nature, we suggest the need to reflect about sustainability inthe current minimize the alienation of man from nature.